The Effect Of Local Tax Towards Local Revenue In Malang District - Sangatta, Angger Wahyudian; no, Sutris (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
This study aims to determine how much the effect of local tax towards local revenue in Malang district at the year 2008 to 2012. Local tax is defined as a local source of revenue that has an important contribution to regional development. Regional development is an effort to regulate the development of the area and the local facilities. Strong regional development is sourced from a good reception area. The one source of local revenue is taxes. Taxes are very influential in the reception area. In accordance with government regulations on implementation of regional autonomy, the government itself has authorized an area to build their respective areas with funding from the area. Government must optimize the sources of funding to achieve good development. Under Law No. 33 of 2004 on Fiscal Balance between the Central Government and Local Government states that local revenue sources are: local revenue, fund balance, and other legitimate revenue. This study applies descriptive data analysis and multiple regressions, by employing computer software SPSS and Microsoft excel. The data used in this study is a time series data for the year 2008 to 2012 from January to December. The data include: local taxes, levies, result of wealth management and other legitimate revenue in Malang district. Results of the research have explained that during the period of 2008 through 2012, local taxes positively bring significant effect on the value of PAD (local revenue) in the Malang district with elasticity of 1,006%. A local tax is a positive effect on local revenue, but the regression has demonstrated that the local tax has the effect of second rank after the levies on local revenue. The largest effect for local revenue is levies. The suggestion withdrawn according to the researcher is by increasing the performance quality and productivity of duties and functions of the DPPKA Malang District in delivering the service to Taxpayers. Keywords: local tax, local revenue, regional development, DPPKA.